Microstructure-dependent phase stability and precipitation kinetics in equiatomic CrMnFeCoNi high-entropy alloy: Role of grain boundaries. (15th January 2022) - Daniel, Rostislav; Zalesak, Jakub; Matko, Igor; Baumegger, Walter; Hohenwarter, Anton; George, Easo P.; Keckes, Jozef
Abstract: The multi-principal element CrMnFeCoNi alloy, which solidifies as a single-phase solid solution with the face-centered cubic (fcc) structure, is thermally stable above 900 °C but is known to decompose into multiple phases at temperatures between 450 and 800 °C. Although the thermal stability of Cr-Mn-Fe-Co-Ni alloys can be altered by changing the composition, there is limited knowledge of the role of microstructure on the kinetics of precipitation from the supersaturated primary fcc phase. To fill this gap, we compared the thermal stability of monocrystalline and polycrystalline thin films of the equiatomic CrMnFeCoNi alloy during synthesis and after post-deposition annealing. At the processing temperature of 700 °C, the polycrystalline film undergoes substantial phase decomposition in 3 min, consistent with earlier results that a bulk alloy of similar composition decomposes into multiple phases at this temperature. In contrast, the monocrystalline film of the same composition remains single-phase both during synthesis and subsequent annealing at 700 °C for 5 h. X-ray diffraction investigations together with comprehensive transmission electron microscopy analysis revealed that the decomposition of the supersaturated primary phase is related to the presence of structural defects, in particular grain boundaries, which promote diffusion of Cr and Mn and subsequently destabilize the primary solid solution. Correspondingly, the absence of high-diffusivity grain boundaries in the monocrystalline alloy prevents its primary phase from decomposing. The fundamental role of grain boundaries on precipitation kinetics, manifested through the short circuiting of sluggish bulk diffusion in entropy-stabilized multi-principal element alloys, is discussed together with the possibility of controlling their thermal stability by microstructural design. Graphical abstract: Image, graphical abstract